The Enduring Experience in Dry Eye Diagnosis: A Non-Interventional Study Comparing the Experiences of Patients Living With and Without Sjögren’s Syndrome - Figueiredo, Francisco C. (Ophthalmol Ther, 2021)
INTRODUCTION: Previous studies have examined the patient experience regarding the diagnosis and management of dry eye disease (DED). The current study explored the ways in which the DED diagnostic pathway differs for those living with and without Sjögren’s syndrome (SS), to identify aspects that influence the patient experience and associated quality of life (QoL). METHODS: An observational/descriptive, non-interventional, retrospective, self-reported online survey was conducted among adults living in France, Spain and Italy who were diagnosed with DED (with/without SS), were using topical DED treatments (≥ 6 months), and were not contact lens users. Recruitment was via an online database for non-SS participants and through local patient advocacy groups for SS respondents. RESULTS: The analysis included 827 respondents; 416 (50.3%) had SS and 82% were female. The mean age was 55 (SD 11; range 16–99) years. The mean age at diagnosis was 46 (SD 12; range 13–78) years and 50 (SD 10; range 21–73) years for SS and non-SS groups, respectively (p < 0.0001). The mean time to diagnosis was extended for SS participants [32 (SD 62) months] versus non-SS individuals [8.6 (SD 28) months (p < 0.0001)] and was associated with reduced QoL scores (r = 0.113; p = 0.0169). More SS participants (31%) consulted ≥ 4 healthcare professionals (HCPs) before DED diagnosis, versus non-SS individuals (6%) (p < 0.0001). Diagnosing clinician varied for SS respondents according to country, probably due to differences in healthcare systems/structures. More SS participants viewed their condition as a handicap than a discomfort, reporting greater QoL impact (p < 0.0001). CONCLUSIONS: Patient experiences in DED diagnosis vary substantially when comparing SS and non-SS individuals. Time to diagnosis significantly impacts QoL for SS patients, who see more HCPs ahead of DED diagnosis. The number of HCPs consulted before diagnosis and perceptions of DED are important for both groups. Country-specific variations highlight opportunities to improve consistency and efficiency across DED diagnostic pathways. These data should be considered alongside existing evidence from high-quality sources (e.g. clinical records). SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s40123-021-00341-6.